2021
DOI: 10.1186/s12913-021-07109-5
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events in women giving birth in a labor ward: a retrospective record review study

Abstract: Background Childbirth could negatively affect the woman’s health through adverse events. To prevent adverse events and increase patient safety it is important to detect and learn from them. The aim of the study was to describe adverse events, including the preventability and severity of harm during planned vaginal births, in women giving birth in the labor ward. Methods The study had a descriptive design with a retrospective birth record review to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 31 publications
0
14
1
1
Order By: Relevance
“…AEs, responsible for morbidity and mortality in hospitalized patients, are reported to be between 3 and 17%, and up to 50% are considered preventable [ 3 ]. In obstetrics, an incidence of up to 5.9% is reported [ 10 ]. In statistics, obstetrics is often not evaluated separately but subsumed under the specialist discipline of gynecology, which makes it difficult to state the exact number of AEs in obstetrics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…AEs, responsible for morbidity and mortality in hospitalized patients, are reported to be between 3 and 17%, and up to 50% are considered preventable [ 3 ]. In obstetrics, an incidence of up to 5.9% is reported [ 10 ]. In statistics, obstetrics is often not evaluated separately but subsumed under the specialist discipline of gynecology, which makes it difficult to state the exact number of AEs in obstetrics.…”
Section: Discussionmentioning
confidence: 99%
“…In statistics, obstetrics is often not evaluated separately but subsumed under the specialist discipline of gynecology, which makes it difficult to state the exact number of AEs in obstetrics. Studies that explicitly consider obstetrics give incidences between 0.4% and 3.6% with a preventability of more than 50% [ 10 , 22 ]. In our evaluation, the incidence of AEs is 23% and 29%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 However, the quality of the medical record should be considered when using medical record review methods to identify adverse events, 3,7 as poor quality can compromise the validity and utilization value of the findings. [8][9][10] Although various retrospective medical record review studies have been conducted to identify adverse events, 5,[11][12][13][14][15] few have examined the impact of medical record quality on them. A study that did examine this association reported that missing medical record information was associated with a lower rate of identification of adverse events, while poor medical record quality was associated with a higher rate of identification of adverse events.…”
mentioning
confidence: 99%